The Effectiveness of Office Management Practices to its Employees in a Shared Services Based Insurance Organization : A Case Study AIG Shared Services (M) Sdn Bhd - Ratilal, Hemal Kumar (2015)
The insurance industry has become a leader in business segments worldwide and there are various company’s working in a shift for its employees and it is recommended to assess the general perceptions among its employees towards office management practices in an organization. This research was done for AIGSS (M), an insurance company with various working shift and was aim to understand how its administration and facility function works efficiently. The contents of the research was to understand how important a support service can be in an organization and also to assess the importance of its objectives. AIG is a very reputable and pioneer insurance company in the world and HQ is in New York. As an American company, it has shown tremendous support towards its employees ranging from work-related trainings and ensuring the well being of employees are taken care. They believe that customers must be their friend to make business, but this can only materialize if the employees are also their friend. The research focused on several key areas including Office Administration, Facilities Management, Asset Management, Security at Work, Front Office Management and Transport Services.